Importance of Cytohistological Correlation and Diagnostic Utility of Endoscopic Ultrasound in Gastric Glomus Tumor: A Case Report - Gupta, Rakesh Kumar; Saran, Ravindra Kumar; Nabi, Prithiviraj; Nag, Hirdaya H; Srivastava, Siddharth (Indian Journal of Medical and Paediatric Oncology, 2019)
We present a case of gastric glomus tumor (GGT) in a 60-year-old female patient presented with progressive dysphagia for both solid and liquid diagnosed with the help of endoscopic ultrasound (EUS)-guided fine-needle aspiration cytology with histological correlation and detailed immunohistochemistry evaluation. Till date, only seven cases were correctly diagnosed by EUS-guided aspiration cytology. We report this case to highlight the cytological features and importance of EUS in diagnosing GGT.
Keywords: Endoscopic ultrasound; fine-needle aspiration cytology; gastric glomus tumor; immunohistochemistry